Relational Networks and Strategic Competition in the Asia-Pacific - Zhili HAN; Hongchi WEI (East Asian Policy)
The post-Cold War era has witnessed the emergence of continually evolving relational networks in the Asia-Pacific, including—but not limited to—the US network of alliances and partnerships, China’s network of strategic partnerships and ASEAN’s network of dialogue partnerships. This article adopts a network-centric approach to examine the dynamics of US–China competition in the Asia-Pacific. It argues that these overlapping relational networks both constrain the behaviour of network members and provide them with the flexibility to navigate the US–China strategic competition and shape the evolution of regional order.